Improvement of the Solar Photoelectric System Installed to Cover 30 Percent of the Electricity Consumption of Administrative Buildings (Eurasian Journal of Engineering and Technology, 2023)
This article provides information aimed at covering the buildings of ministries and state organizations with solar panels using energy-saving and renewable energy sources and reducing energy consumption in these organizations and it is recommended to use ongrid photoelectric systems to reduce energy consumption.